Correlation of circulating angiogenic factors with circulating tumor cells and disease recurrence in patients undergoing curative resection for colorectal liver metastases - Rahbari, Nuh Nabi; Reißfelder, Christoph; Mühlbayer, Monika; Weidmann, Kathrin; Kahlert, Christoph; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (Annals of surgical oncology, 2011)
Circulating angiogenic factors (CAF) have been shown as therapeutic targets and prognostic biomarkers in metastatic colorectal cancer. However, their correlation with circulating tumor cells (CTC) is unknown, as is their role as prognostic biomarkers in patients amenable for curative resection.
Gesehen am 08.09.2022